2023
DOI: 10.1186/s41155-023-00251-5
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, sleep habits and executive function during the COVID-19 pandemic through parents’ perception: a longitudinal study

Abstract: The present study therefore aims to examine trait and state anxiety, sleep habits and executive functioning during 1 year and a half of the COVID-19 pandemic in children and adolescents through the lens of parents. Assessments were conducted at three different times: April 2020 (T1), October 2020 (T2) and October 2021 (T3). The main sample included 953 children and adolescents aged 6 to 18 years, and scales were used to assess anxiety (STAIC), sleep habits (BEARS) and executive functioning (BRIEF-2). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 69 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…The main results showed that the rates of anxiety, sleeping habits, and executive functioning impairments in children and adolescents appear to have deteriorated over time [27]. In terms of EFs, results revealed a decline in global executive functioning as well as deteroration in emotional regulation, cognitive fl exibility, and planning and organizational skills [27]. Other authors have reported a worsening in executive and academic functioning during the COVID-19 confi nement period, which is consistent with these fi ndings [20,[52][53][54].…”
Section: Covid-19 Pandemic Pathways That May Alter the Development Of...mentioning
confidence: 97%
See 4 more Smart Citations
“…The main results showed that the rates of anxiety, sleeping habits, and executive functioning impairments in children and adolescents appear to have deteriorated over time [27]. In terms of EFs, results revealed a decline in global executive functioning as well as deteroration in emotional regulation, cognitive fl exibility, and planning and organizational skills [27]. Other authors have reported a worsening in executive and academic functioning during the COVID-19 confi nement period, which is consistent with these fi ndings [20,[52][53][54].…”
Section: Covid-19 Pandemic Pathways That May Alter the Development Of...mentioning
confidence: 97%
“…Stress aff ects the immune system, hormonal system and can raise the risk of neuro-infl ammation, increasing the possibility of damaging the CNS and altering cognitive functioning [1,26]. In line with this approach, there have been reports of an increase in attention and memory problems, increased irritability and alterations in Executive Functions (EFs) in children and adolescents [6,[9][10][11]27].…”
Section: Duringmentioning
confidence: 99%
See 3 more Smart Citations